2015
DOI: 10.1590/1678-4499.0334
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and soil moisture in a silvopastoral system in southeastern Brazil

Abstract: In this study, the microclimate changes in silvopastoral systems are quantified at different time and spatial scales and compared with single-pasture systems. The study was conducted in a silvopastoral system in São Carlos, Brazil (22°01' South and 47°53' West). The silvopastoral system consisted of grass pastures [Urochloa (sin. Brachiaria) decumbens cv. Basilik] lined with strips of native trees spaced at 17 m. Continuous microclimate measurements (air temperature, relative humidity, wind speed, and incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 14 publications
7
35
0
8
Order By: Relevance
“…Minimum air temperature in the understory was 0.16ºC lower in degraded area than in the mango orchard. Similar results were observed by Pezzopane et al (2015), in São Carlos, São Paulo State, where minimum air temperature was 0.10ºC lower in the forest understory with less vegetative cover than the other. In areas with less vegetation, minimum air temperature is usually lower, because having less vegetation facilitates the passage of longwave radiation (coming from Earth), leading to atmospheric cooling.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Minimum air temperature in the understory was 0.16ºC lower in degraded area than in the mango orchard. Similar results were observed by Pezzopane et al (2015), in São Carlos, São Paulo State, where minimum air temperature was 0.10ºC lower in the forest understory with less vegetative cover than the other. In areas with less vegetation, minimum air temperature is usually lower, because having less vegetation facilitates the passage of longwave radiation (coming from Earth), leading to atmospheric cooling.…”
Section: Resultssupporting
confidence: 85%
“…The mango orchard reduced mean air temperature in the understory by 0.37ºC in comparison to the degraded area. Similar results were observed in São Carlos, where average air temperature was reduced by 0.25ºC in the forest understory with more vegetation coverage in comparison with the other understory (Pezzopane et al, 2015). This was lower than the results found in Jussari, Bahia State, where the reduction of the average air temperature was 1.25°C in the understory of the forest areas and a shaded cacao crop (Theobroma cacao L.) (Pinheiro et al, 2013).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Some studies have shown that shadow promoted by trees in silvopastoral systems reduce solar radiation, avoid soil moisture loss and increase air humidity (Paciullo et al, 2008;Law et al, 2011;Pezzopane et al, 2015) which contribute to entomophathogen establishment (Meyling et al, 2009).…”
Section: Introductionmentioning
confidence: 99%